BioAgents: Bridging the gap in bioinformatics analysis with multi-agent systems - Mehandru, Nikita; Hall, Amanda K.; Melnichenko, Olesya; Dubinina, Yulia; Tsirulnikov, Daniel; Bamman, David; Alaa, Ahmed; Saponas, Scott; Malladi, Venkat S. (Scientific Reports, 2025)
Developing end-to-end bioinformatics workflows is challenging, demanding deep expertise in both genomics and computational techniques. While large language models (LLMs) provide some assistance, they often lack the nuanced guidance required for complex bioinformatics tasks, and are resource-intensive. We thus propose a multi-agent system built on small language models, fine-tuned on bioinformatics data, and enhanced with retrieval augmented generation (RAG). Our system, BioAgents, enables local operation and personalization using proprietary data. We observe performance comparable to human experts on conceptual genomics tasks, and discuss future work to enhance code generation capabilities.